Exploited fishery resources of Achankovil river - Anjana Preetha, P. (KUFOS, 2019)
A sincere attempt to analyse the nature of the fishery of the non- dammed Achankovil river based on primary data collected on a biweekly basis from the four-routine landing centres viz. Karichal, Prayikara, Chennithala and Kidangayam during April 2018 to March 2019 was carried out. The results revealed that the fishery is artisanal and multispecies in nature and the catch is composed of 61 finfishes and 2 crustacean species of 28 families, contributed together to 76.7 tonness which also included four threatened and three nearly threatened species. The bulk contribution to the fishery was from gillnet (82%) followed by seine net (16%) Cast net (1%) and others (1%) operated from the FRP and plank- built canoes. The major candidate species contributing to the fishery were identified to be Labeodussumieri(11.6%), Channastriata(9.7%), Amblypharyngodonmelettinus, (8.9%) Horabagrusbrachysoma(8.7%), and Heteropneustesfossilis (8.1%). Out of the total landing quantified 8.2% was contributed by ten species of exotics and 5.3 % was by three species of transplanted species. Demographic aspects including the growth and mortality parameters were computed separately for four prioritised species viz. Dawkinsiafilamentosa, Systomussarana,Nandusnandus whichrevealednegative allometry where as Pristolepisrubripinnis exhibited isometric growth; also the studied species were found to be exploited below their optimum rate. Use of seine netting with mesh size less than legal limits, lack of standardised methodology for catch documentation, catching of threatened species, and the plausible threat from the proposed river linking project were identified as the major problems which necessitates the need for strict enforcement of existing legislations, data collection on participatory level including data keeping by cooperatives and creation of awareness on conservation of fishery resource.